Pemanfaatan Minyak Jelantah Menjadi Sabun Cuci Pada Ibu-Ibu Taman Bacaan Perigi, Depok - Sevty Wahiddirani Saputri; Siarwi Siarwi; Benarda Benarda (Abdimisi, 2021)
Women in this case housewives have the potential to save the family economy in the midst of the Covid-19 pandemic. Many women are saving families by taking over the duties of households affected by the pandemic. Housewives develop their potential to earn family income, for example by installing sequins and motees, patchwork making, cakes to make, cloth masks and mask connectors. Let's move together and we hope that the government will always support the improvement of women's competence, through training, empowerment, financing, and absorption of the work. There are so many roles of women that all start from the family, but do not exclude their domestic roles. So women play a role in managing and balancing these times well. Keep trying to be professional in any situation.